ABSORBSI NaCl PADA TELUR DARI MEDIA PENGASINAN DENGAN VARIABEL WAKTU PEMERAMAN - Mardiyono Mardiyono; Sri Widati; Nur Hidayati (Caraka Tani: Journal of Sustainable Agriculture, 2008)
Egg is breed product that contains nutrients which easy to digest and exploited by the body. Egg is easily damaged and so it need to be preserved. One way to preserve is salted using sodium chloride (NaCl). The salt functions are to prevent the growth of bacteria, improve the taste and practical value. The longer it is ripened in the salting media, it will be more salty, because more salts are absorbed in the egg. The ewperiment was aimed tho know the NaCl content absorbed in the egg from salting media with various ripening time.Determination of NaCl content in the egg used Mohr Argentometric method i.e. the use of AgNO3 standard solution and K2CrO4 indicator. The determination of NaCl was done in duck eggs obtained from salting in week-0, 1, 2 and 3. Each treatment used 3 replications. The statistic used was one way analysis of varian (ANOVA) continued with SNK test.NaCl contents in the egg before salted were 0.34%  in the egg white and 0.33% in the egg yolk. The NaCl content that was absorbed in the egg white from salting media after salted in week-1,2 and 3 were 2.77%, 3.71% and 5.09% respectively. While in the egg yolk the contents were 0.43%, 0.71% and 0.97% respectively. After statistically tested by one way anova and continued by SNK test it could be consluded that there was significant difference of NaCl content absorbed in the egg white and yolk from salting media inter-time of ripening.